Implementasi Pendidikan Inklusi Terhadap Pembelajaran Anak Berkebutuhan Khusus Di MAN 2 Kota Payakumbuh - Tiara Yulia Putri; Khairatul Zahra; Kharisma Hakim (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The implementation of the inclusion education in Madrasah Aliyah Negeri (MAN) 2 of Payakumbuh City is given to students who experience special needs, The existence of this education makes MAN 2 Payakumbuh City as the Child Friendly School 2 Payakumbuh City was selected as the "Child Friendly School in 2017 because it accepts normal prospective students as well as special needs students (ABK). Not only that madrasah civic must also treat all students equally without distinguishing them. In 2017 MAN 2 Kota Payakumbuh had three special needs students, all of whom were blinders, and all three were blind. Until now, the implementation of inclusion education in MAN 2 of Payakumbuh City continues conducive Various policies were undertaken by Madrasah to support the learning process of all students by equating all students and learning adjustments to the needs of all students The limitations of children Special needs don't prevent them from demanding science. Special needs children have various potentials that can be developed The purpose of this study was to look at and describe the phenomenon that occurred in the implementation of inclusion education in Payakumbuh City Management 2 This study uses a qualitative descriptive method of describing the implementation of inclusion education in Man 2 City The breasts grow